Genesi di un pensiero critico: Il giovane Marx - Musto, Marcello (Bollettino Filosofico, 2025)
Karl Marx’s relation with philosophy was decisive. It marked his way of thinking and influenced the style of many of his writings. The period here scrutinized, 1838-1844 – years of intensive philosophical study –, proved essential for Marx. Among other things, it gave him solid foundations for understanding that civil society was the basis of the political state, and not the other way around, as argued by Hegel. For Marx the roots of philosophy had to be sought in the world, not outside it. Recognizing human alienation did not mean having overcome it. Self-consciousness that did not convert into political conflict did not help to advance the cause of human emancipation by a single step. The work of Marx (and Engels) is fundamental for opposing philosophies that do not seek the emancipation of the oppressed classes. Keywords: Engels, Marx, Materialist Conception of History, Political Philosophy, Young Hegelians